KINERJA DINAS SOSIAL, TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KUBU RAYA DALAM PELAYANAN PEMBUATAN KARTU TANDA PENCARI KERJA (AK 1) - Fajar Prastiko E.42009078 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This study aims to describe the performance of Social Affairs, Manpower and Transmigration Kubu Raya regency in making service cards jobseekers (AK 1). Title essay concerns issued by AK 1 manufacturing service performance conducted by Field Workforce Training and Placement, Department of Social, Manpower and Transmigration Kubu Raya regencyThis study uses a qualitative descriptive approach. Techniques of data collection is by interview, observation and document study. Analysis using domain analysis techniques. Location of the study is the Social Service Office, Manpower and Transmigration Kubu Raya regency. Research subject is the Head of Department, Head of Workforce Training and Placement, Placement Head and Workforce Expansion, Head Productivity Improvement Training and Labour, the Task Service, and job seekers who manage card manufacturing   AK 1.Conclusions in this study are not optimal service performance given by Field Workforce Training and Placement due to lack of adequate infrastructure facilities, often a technical disruption in service implementation manufacture AK 1, lack of energy ministry officials in the implementation of specific AK 1, and officials have yet to fully disciplines. Therefore, the recommendation is to improve the operational performance of the facility by improving operational tools, provide room service and facilities support services satandar infrastructures. Then perform specialized recruitment services as officers or employees of the Work Introduction to Civil and also to increase the discipline with the application of strict punishment and electronic absent Keywords: performance, service, card AK 1